Odpowiedzi

2009-11-20T16:59:18+01:00
3(a+b)+(a-2b) = 3a +3b + a -2b=4a + b
-4(x-z)-(x+y) = -4x + 4z - z - y = 4x +3z - y
5(4x-7)+(7-4x)= 20x - 35 = 7 - 4x= 16x - 39
(4x-y)-2(x+y)= 4x - y - 2x - 2y = 2x - 3x

Łap
23 3 23
2009-11-20T17:04:17+01:00
A)3(a+b)+(a-2b)=3a+3b+a-b=4a+2b
b)-4(x-z)-(x+y)=-4x+4z-x-y=-5x+4z-y
c)5(4x-7)+(7-4x)=20x-35+7-4x=16x-28
d)(4x-y)-2(x+y)=4x-y-2x-2y=2x-3y
19 3 19
2009-11-20T17:07:50+01:00
A) 3(a+b)+(a-2b)=3a+3b+a-2b=4a+b
b) -4(x-z)-(x+y)=-4x+4z-x-y=-5x-y+4z
c) 5(4x-7)+(7-4x)=20x-35+7-4x=16x-28
d) (4x-y)-2(x+y)= 4x-y-2x-2y=2x-3y
35 4 35